School Violence and Its Relationship with Psychological Stress and Parental Treatment among Middle School Stu-dents - Nadira, Liazid (Indonesian Journal of Social Science Research, 2024)
The current study aimed to explore the relationship between school violence, psychological stress, and parental treatment among middle school students. A descriptive method was employed, with a random sample of 100 male and female students selected from three middle schools. Data were collected using the School Violence Scale, the Psychological Stress Scale, and the Parental Treatment Scale to assess the level of school violence within the sample. The study re-vealed the following results:  There is a relationship between school violence and psychological stress among middle school students.  There is a relationship between school violence and parental treatment among middle school students.  Gender-based differences in school violence exist, attributed to the gender variable. There are no statistically significant differences in school violence between urban and rural students.